PENGENDALIAN HAMA TERPADU Helopeltis antonii PADA TANAMAN JAMHU MENTE - ELNA KARMAWATI; TRI HARYANI SAVITRI; WARSI RACHMAT; TRI EKO WAHYONO (Jurnal Penelitian Tanaman Industri, 2001)
Integrated Pesl Control Research of // antonii on cashew was studied out in Wonogiri, Central Java from May lo December 2000. Ihe objective of the study was lo obtain Ihe efective eonlrol method Spill plot design was used. Ihe main plots were intercropping system of cashew with (a) niunghcan and (b) mixed of cassava, peanut and maize, The subplots were treatments of (a) benomyl without B bassiana. (b) R bassiana without benomyl, and (c) eonlrol The concentation of benomyl used were 2 g per liter, while for II. bassiana 11) g per liter containing I. I x 10* conidias. Treatments were applied on Ihe beginning of October 2000, and observations were done twice in one month. The area needed for all plots were 24 000 m1 (4 replications). Hie asscsments consisted of (a) number of //. antonii eggs, nymphs and its natural enemies, (b) number of flowers and shoots attacked, and (c) cashew nut per tree. The result showed thai there was interaction between the Iwo factor tested. Mix-cropping with R bassiana reduced //. antonii population on cashew and increased productivity from 3.85 kg lo 5.33 kg per tree. These treatments were therefore recommended for controlling the pest.